The study of consumer buying behavior towards korean popular (kpop) boyband “bts” physical music album in Indonesia - Qaistira, Navissa Ulfath; Aprilianty, Fitri (Journal of Business and Management, 2020)
Abstract. As Korean pop is growing rapidly in the worldwide. BTS as one of the K-pop boyband has become the world's most successful boy band. This condition also occurs particularly in Indonesia. BTS fans in Indonesia have proven to be the top 10 countries with the largest BTS fans in the world. However, this has no effect on the sales of BTS physical music albums in Indonesia. Although in less than 7 years BTS has sold more than 20 million physical albums and making them the best-selling Korean act of all time, Indonesia still does not include into the highest BTS album sales data. Therefore, this study aimed to examine more closely about the consumer buying behavior that influence the phenomenon of BTS hysical music albums sales that were conducted by BTS fans in Indonesia and recommendations that can be done by K-pop boyband marketers in selling the physical music album products. This research will be conducted through a quantitative approach by an online survey and participants of this research are 247 Indonesia consumer’s who have bought BTS physical album. Researcher explores factors (audio component, visual component, idolatry) which are adopted from related journals and using Theory of Planned Behavior that was modified to be the model of this study. This research using PLS-SEM to analyze the relationship between the factors, attitude toward BTS physical music album, subjective norms, perceived behavioral control, purchase intention, and purchase behavior. The result indicates that idolatry, attitude toward BTS physical music album, perceived behavioral control are affecting Indonesian purchase behavior toward BTS physical music album. The finding of this research is expected to enhance the K-pop boyband marketers’ knowledge about Indonesian consumers and can  maximize the selling of K-pop boyband physical music album products in Indonesia. Keywords: K-pop, Theory of Planned Behavior (TPB), Purchase Intention, Purchase Behavior